Impact of aging on dendritic cell functions in humans - Agrawal, Anshu; Gupta, Sudhir (Ageing research reviews, 2011)
Aging is a paradox of reduced immunity and chronic inflammation. Dendritic cells are central orchestrators of the immune response with a key role in the generation of immunity and maintenance of tolerance. The functions of DCs are compromised with age. There is no major effect on the numbers and phenotype of DC subsets in aged subjects; nevertheless, their capacity to phagocytose antigens and migrate is impaired with age. There is aberrant cytokine secretion by various DC subsets with CDCs secreting increased basal level of pro-inflammatory cytokines but the response on stimulation to foreign antigens is decreased. In contrast, the response to self-antigens is increased suggesting erosion of peripheral self tolerance. PDC subset also secretes reduced IFN-α in response to viruses. The capacity of DCs to prime T cell responses is also affected. Aging thus has a profound affect on DC functions. Present review summarizes the effect of advancing age on DC functions in humans in the context of both immunity and tolerance.